P353 THE "TIMES" IN COVID–TIME: EXPERIENCE OF A CICU "SPOKE". (18th May 2022) - Piemonte, F; Carraturo, A; Cudemo, V; Damiano, S; De Angelis, A; Forte, R; Leccia, A; Lirato, C; Molaro, M; Penna, G; Petitto, M; Puzio, E
Abstract: We analyzed data regarding patients hospitalized in the period 03/09/2020–03/09/2021 in the ICU–Cardiology Division of the "San Giovanni di Dio Hospital" of Frattamaggiore (NA), configured as "Spoke" CICu for the AMI Network of the Campania Region, and we compared them with the same parameters of patients hospitalized during 2019. In particular, we analyzed differences in epidemiologic parameters and, in patients hospitalized for acute coronary syndromes, we evaluated the waiting times for hemodynamic procedures. The total number of hospitalized patients decreased by about 25%, while the mean age of patients and the percentage of hemodynamic procedures were comparable. In particular we noted that, while the percentages of patients hospitalized for acute myocardial infarction were similar in COVID and PRE–COVID era, during the pandemic in patients affected by acute myocardial infarction.the percentages of STEMIs were superior to those of NSTEMIs. Finally, we examined door–to–balloon times. In patients affected by STEMI we found that, even during the pandemic, primary angioplasty was performed on average within 100 minutes, meaning that ultra–fast swabs (mandatory before the procedure) did not produce delay. Moreover, in the pandemic period patients with NSTEMI, despite a stay of about 8 hours in ER to obtain the result of the antigenic swab for SARS–COV2, received coronary arteriography in a shorter time than in the pre–pandemic era (52, 8 and 62, 4 hours respectively). This analysis seems to show that the pandemic has not affected the access and hospitalization times of patients with acute coronary syndrome, and that, although greatest difficulties have arisen, the times of access to hemodynamics have not been affected by COVID.